Amperometric Immunosensor Based on a Protein A/Deposited Gold Nanocrystals Modified Electrode for Carbofuran Detection - Sun, Xia (Molecular Diversity Preservation International (MDPI), 2011)
In this paper, an amperometric immunosensor modified with protein A/deposited gold nanocrystals (DpAu) was developed for the ultrasensitive detection of carbofuran residues. First, DpAu were electrodeposited onto the Au electrode surface to absorb protein A (PA) and improve the electrode conductivity. Then PA was dropped onto the surface of DpAu film, used for binding antibody Fc fragments. Next, anti-carbofuran monoclonal antibody was immobilized on the PA modified electrode. Finally, bovine serum albumin (BSA) was employed to block the possible remaining active sites avoiding any nonspecific adsorption. The fabrication procedure of the immunosensor was characterized by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV), respectively. With the excellent electroconductivity of DpAu and the PA’s oriented immobilization of antibodies, a highly efficient immuno-reaction and detection sensitivity could be achieved. The influences of the electrodeposition time of DpAu, pH of the detection solution and incubation time on the current response of the fabricated immunosensor were investigated. Under optimized conditions, the current response was proportional to the concentration of carbofuran which ranged from 1 to 100 ng/mL and 100 ng/mL to 100 μg/mL. The detection limit was 0.1924 ng/mL. The proposed carbofuran immnuosensor exhibited high specificity, reproducibility, stability and regeneration performance, which may open a new door for ultrasensitive detection of carbofuran residues in vegetables and fruits.